2021
DOI: 10.3390/nano11040942
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Synthesis of Predominant Semi-Ionic and Covalent Fluorine Bonding States on a Graphene Surface

Abstract: In this study, fluorinated graphene (FG) was synthesized via a hydrothermal reaction. Graphene oxides (GOs) with different oxygen bonding states and oxygen contents (GO(F), GO(P), and GO(HU)) were used as starting materials. GO(F) and GO(P) are commercial-type GOs from Grapheneall. GO(HU) was prepared using a modified Hummers method. The synthesized FGs from GO(F), GO(P), and GO(HU) are denoted as FG(F), FG(P), and FG(HU), respectively. The F atoms were bound to the graphene surface with predominantly semi-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…XPS measurements show that both elements are present in the sample. Three types of environments are found for sulfur, C–S–C, S–O, and C–SO x –C ( x = 2, 3), ,− and two kinds of environments are detected for fluorine, semi-ionic C–F and CF 3 . ,− Thus, the present work shows that carbonization of ionic diacetylenes may be an alternative method to introduce doping elements in a graphite structure …”
Section: Resultsmentioning
confidence: 51%
“…XPS measurements show that both elements are present in the sample. Three types of environments are found for sulfur, C–S–C, S–O, and C–SO x –C ( x = 2, 3), ,− and two kinds of environments are detected for fluorine, semi-ionic C–F and CF 3 . ,− Thus, the present work shows that carbonization of ionic diacetylenes may be an alternative method to introduce doping elements in a graphite structure …”
Section: Resultsmentioning
confidence: 51%
“…Peaks at 964 and 1538, 1602 and 1722 cm –1 , 1451 and in the range 2500–2950 cm –1 , as well as in the range 2950–3750 cm –1 are associated with vibrations of the carbon skeleton, CC bonds, vibrations of oxygen-containing functional groups CO, vibrations of carbon single bonds in sp 3 hybridization of C–H, CH, CH 2 , and CH 3 , as well as hydroxyl groups adsorbed on the sample surface, respectively . The new line at 1111 cm –1 is associated with the appearance of the C–F bond . It should be noted that the ratio of the intensities of the peaks associated with CC and CO vibrations is close to 1, which indicates a weak degree of removal of oxygen groups with a double bond when ascorbic acid is used to reduce RGOF.…”
Section: Resultsmentioning
confidence: 92%
“…44 The new line at 1111 cm −1 is associated with the appearance of the C−F bond. 45 It should be noted that the ratio of the intensities of the peaks associated with C�C and C�O vibrations is close to 1, which indicates a weak degree of removal of oxygen groups with a double bond when ascorbic acid is used to reduce RGOF.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…126 Lee et al compared three types of GOs with various O-group contents and demonstrated that O-groups featuring sp 3 -hybridised carbon, such as C–O–C and CO, favoured the formation of covalent C–F bonds via fluorination, whereas carboxyl and hydroxyl groups easily detached from the carbon skeleton and generated sp 2 -hybridised active centres, which promoted the formation of semi-ionic C–F bonds. 128…”
Section: Synthesis–structure–performance Relationshipsmentioning
confidence: 99%